The effects of parental retirement on adult children's health: Evidence from China - Zhuang Hao; Huihui Cheng; Till Bärnighausen; Simiao Chen (Health Economics, 2023)
Using representative data from China, we examine the causal effects of parental retirement on the health of adult children. To do so, we adopt a fuzzy regression discontinuity design and exploit the mandatory retirement ages in China as cut-off points. We find no evidence that parental retirement has significant effects on the mental health, healthcare utilization, or risky health behaviors of adult children. However, paternal retirement and maternal retirement have different effects on adult children's Self-reported health (SRH). Paternal retirement has a significantly negative effect only on the SRH of sons, while maternal retirement does not induce such effects. Potential mechanisms of intergenerational transfer through which parental retirement might affect adult children's health are also explored.
Keywords: 330; fuzzy regression discontinuity; health; intergenerational effect; parental retirement